Identification of a Spheroid based on the First Order Polarization Tensor - Mohamad Yunos, Nurhazirah; Ahmad Khairuddin, Taufiq Khairi; Lionheart, William RB (Journal of Science and Technology, 2017)
Polarization tensor (PT) has a lot of useful and important practical applications. In this case, it must be firstly determined by some appropriate method. Besides, understanding some properties of the PT might also be very useful in order to apply it. In this study, we investigate the first order PT for ellipsoid and use it to describe the first order PT for spheroid as well as identify the spheroid. Numerical examples are also given to further justify our results.